Nutrient nourishment through organic approach: a critical review on foliar nutrition - Chandan , EM; Krishnan , R; Parameswari , E; Janaki, P; Prabhukumar , G (Plant Science Today, 2024)
Nutrients play a pivotal role in the growth, development and overall health of plants. However, the widespread use of inorganic fertilizers in modern agriculture has led to significant environmental and health concerns, including soil degradation, water contamination and the disruption of beneficial soil microbiota. These issues underscore the urgency of exploring alternative, sustainable fertilization methods. This review critically examines the potential of organic fertilizers in addressing the nutritional deficiencies in soil that are exacerbated by the reliance on inorganic inputs. Our research hypothesizes that organic fertilizers not only replenish essential nutrients but also restore soil health by enhancing microbial diversity and activity. This hypothesis is significant and timely, given the growing global demand for sustainable agricultural practices. For the first time, our synthesis reveals overlooked interdisciplinary connections between soil microbiology, plant nutrition and sustainable agricultural economics, offering a novel perspective on the integration of organic fertilizers into mainstream agricultural practices. The breakthrough identified in this review lies in the comprehensive understanding of how organic fertilizers contribute to long-term soil fertility and crop productivity, beyond merely supplying nutrients. Moreover, this review identifies promising business opportunities in the development and commercialization of organic fertilizers tailored to specific crop and soil needs. Prospective directions for further research include the exploration of advanced organic formulations and the assessment of their economic viability on a large scale.